Resilience of Madrasah Aliyah Teachers Amid Curriculum Transformation: A Reflective Study from the Merdeka Curriculum to the Love-Based Curriculum - Alfi Nikmah; Nusaibah (Tapis: Jurnal Penelitian Ilmiah, 2025)
This study aims to describe the form of resilience of Islamic Senior High School or Madrasah Aliyah (MA) teachers in Pati Regency in facing the implementation of the Merdeka Curriculum, identify the challenges faced in the curriculum adaptation process, and examine the potential of the Love-Based Curriculum as an alternative approach in the context of madrasah education. This study uses a descriptive qualitative approach with a case study method. Data collection techniques include in-depth interviews, observation, and documentation. Data analysis is conducted using the interactive model of Miles and Huberman, which involves data reduction, data presentation, and drawing conclusion. The results of the study indicate that teachers' resilience is influenced by internal factors such as self-directed learning initiatives and religious motivation, as well as external factors such as institutional support and training. Public madrasahs have higher readiness compared to private madrasahs because they are supported by established human resources and systems. However, some private madrasahs demonstrate strong resilience through local culture and religious values that have been built over time. Additionally, reflections on the Love-Based Curriculum indicate that an approach based on compassion and empathy is beginning to be integrated by some madrasahs as a response to the need for more humanistic learning. This study recommends the importance of strengthening systematic support, inter-institutional collaboration, and training to support the sustainability of curriculum transformation.